Navigating Isolated Post-Traumatic Radial Head Dislocation in Adolescents: A Case Report from Bangladesh Emphasizing Management Strategies - Hamid, Kawser; Hasan, Mohammad Mainul (Central Medical College Journal, 2024)
Background: Isolated anterior dislocation of the radial head is a rare orthopedic injury, often presenting with distinct clinical features and requiring specialized management. We report the case of an 18-year-old female who presented to our hospital 5 months post-injury, complaining of restricted left elbow joint movement and pain following a fall from a low chair at home. Clinical examination revealed tenderness and anterior dislocation of the radial head, confirmed by radiographs showing isolated anterior dislocation without associated fractures. Closed reduction attempts failed, leading to an open reduction of radial head in combination with correction of malignant with ulnar osteotomy and reconstruction of annular ligament and radio-ulnar Kirschner wire placement for stabilization. An upper arm cast was applied with the forearm in neutral rotation for six weeks. At the 12-month follow-up, the patient exhibited a satisfactory range of motion within reference values, comprising 0-140 degrees of flexion-extension arc, 70 degrees of pronation, and 85 degrees of supination. This range aligned with standards set by the American Society for Surgery of the Hand. The patient reported no impediments in daily activities and returned to her pre-injury level of sports activity based on the Tegner scale. This case underscores the complexity of managing isolated anterior radial head dislocation, highlighting the significance of prompt diagnosis, appropriate reduction techniques, and meticulous postoperative care to achieve optimal functional outcomes. Central Medical College Journal Vol 7 No 1 January 2023 Page: 57-62